Pengaruh Experiential Marketing, Brand Image dan Brand Loyalty terhadap Keputusan Pembelian Mcdonald’s Sipin Kota Jambi (Studi Kasus pada Mahasiswa Universitas Batanghari Jambi) - Sopini, Pupu; Iskandar, Fadil; Abdi, Gading Winara (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
Customer purchasing decisions are influenced by various considerations from multiple aspects. Understanding these aspects helps companies design effective marketing strategies and increase the likelihood of product selection. Several factors considered in purchasing decisions include Experiential Marketing, Brand Image, and Brand Loyalty. The aims of this study are: 1) To find out the description of Experiential Marketing, Brand Image, Brand Loyalty, and purchasing decisions at McD Sipin Kota Jambi among Universitas Batanghari students; 2) To analyze the effect of experiental marketing, Brand Image, dan Brand Loyalty simultanly on consumer decisions at Mcd Sipin Kota Jambi at McD Sipin Kota Jambi among Universitas Batanghari students; and 3) To analyze the effect of experiental marketing, Brand Image, dan Brand Loyalty partially on consumer decisions at Mcd Sipin Kota Jambi at McD Sipin Kota Jambi among Universitas Batanghari students. The research method used in this research is a quantitative descriptive method. The research data is in the form of primary data and secondary data. Data collection methods are carried out through observation and questionnaires. The sampling technique used purposive sampling method with the Slovin formula obtained 97 samples. Data analysis with Descriptive Analysis and Multiple Regression Analysis. The results showed: 1) the effect of xperiential Marketing, Brand Image, and Brand Loyalty simultaneously influence consumer purchasing decisions at McD Sipin Kota Jambi among Universitas Batanghari students; (2) The t-test results show that Experiential Marketing, Brand Image, and Brand Loyalty have a positive and significant effect on purchasing decisions, with t-values of 2.514 (Experiential Marketing), 3.905 (Brand Image), and 4.035 (Brand Loyalty), all exceeding the critical t-table value of 1.66088; and (3) The F-test results confirm that Experiential Marketing, Brand Image, and Brand Loyalty significantly affect purchasing decisions, with an F-value of 62.077, surpassing the critical F-table value of 3.09. The coefficient of determination (R²) is 65.6%, indicating that thesethree variables influence purchasing decisions, while the remaining 34.4% is affected by other factors.